Sectional category of maps related to finite spaces - Tanaka, Kohei (Topological Methods in Nonlinear Analysis, 2024)
In this study, we compute some examples of sectional category secat$(f)$and sectional number sec$(f) for continuous maps $f$ related to finite spaces.Moreover, we introduce an invariant secat$_k(f)$ for a map $f$ between finite spaces using the $k$-th barycentric subdivision and show the equalitysecat$_k(f)=$ secat$(\mathcal{B}(f))$ for sufficiently large $k$, where $\mathcal{B}(f)$is the induced map on the associated polyhedra.